(untitled) (Sociología y tecnociencia, 2013)
The author explores the institutional and policy changes that have shaped nanotechnology development in Mexico. It illustrates how the science and technology platform has changed from a science push strategy (based on the Sabato´s Triangle) to a marked driven (Triple Helix) approach. Mexican public policy in NT, while not explicitly stated, is based on the Triple Helix model, and it is in this milieu that businesses, government and universities interact to transform the potential of this technology into an increase in competitiveness. However, there are important aspects that are ignored in the confluence of the socioeconomic dynamic of the country that might obscure the positive social impacts of nanotechnology.